The effectiveness of study skills courses: Do they increase general study competences? - Verena Schmied; Martin Hänze (Forum Neue Medien in der Lehre Austria, 2015)
The present longitudinal study aims to assess the effectiveness of study skills courses in improving students' general study competences. In a pre-study, an online questionnaire was developed which measured the learning process organization, motivation, planning, and stress management on four reliable scales. The participants in the main study were 45 students from five different German universities who attended such a course and a control group of 87 students who did not. Two-way repeated measures ANOVA's indicate an increase in general study competences for students in the intervention group. The change in competences between a pre-test and post-test differ significantly between the groups. 16.12.2015 | Verena Schmied & Martin Hänze (Kassel)